Spatial Dynamics and Risk Mapping of Forest Fires in Madhesh Province, Nepal: A Multi-Criteria Decision Approach - Gunjan Adhikari; Khagendra Prasad Joshi; Dristee Chad; Ashish Ghimire; Sandeep Mahara (Environment and Natural Resources Journal)
Forest fires in Nepal are a pressing environmental concern, impacting ecosystems and community livelihoods. This research aims to understand forest fires, their trends, distribution, and relation with selected variables found in the sub-tropical forests of Madhesh Province of Nepal, and then identify potential fire risks and vulnerable areas. The selected fire incidents were analyzed using fire points produced by the moderate resolution imaging spectroradiometer (MODIS) sensor. Following the analytic hierarchy process (AHP) approach, this research investigates topographic, climatic, biophysical, and anthropogenic variables to create a fire risk map. Throughout the 22-year research period (2001-2023), 6,368 fire incidents and 6,158.22 km2 of total burnt area were reported in the study area. Overall, the Mann-Kendall test showed an increasing trend for regional fire incidents. It has been found that about 24% of the province is either at high or very high risk for fire. The validity of the prediction map was confirmed with an AUC value of 0.798. The findings of the study will be valuable to local, state, and federal governments, policymakers, forest fire managers, researchers, and land planners in building a landscape-level forest fire management plan for high-risk areas.